PCVs in individuals at increased risk of pneumococcal disease: a literature review. (July 2015) - Fletcher, Mark A; Balmer, Paul; Bonnet, Eric; Dartois, Nathalie
<x xml:space="preserve">Abstract</x> The use of pneumococcal conjugate vaccine (PCV) in childhood pneumococcal immunization programs successfully reduced the incidence of pneumococcal disease in children. Nonetheless, there remains a high burden of pneumococcal disease in adults, especially the elderly, and children/adults with chronic medical conditions. Two pneumococcal vaccines are currently available for adults at risk of pneumococcal disease: the 23-valent pneumococcal polysaccharide vaccine (PPV23) and the more recently licensed PCV13. As it is not possible to determine vaccine efficacy in all populations at risk of pneumococcal disease, immunogenicity studies, measuring pneumococcal-specific antibody concentrations and/or the opsonophagocytic activity of serum can provide valuable comparative data for PPV and PCV immunization. This article provides consolidated data on the immunogenicity of PCVs (largely PCV7, and a few studies with PCV9 or PCV13) based on a review of immunogenicity/safety studies in populations (mainly pediatric) at increased risk of pneumococcal disease.